Electronic structure of polyenes related to the visual chromophore. A simple model for the observed band shapes. - Hemley, R (1977)
A model is presented which attributes the widths of absorption bands in carotenoids to conformational disorder induced by the beta-ionylidene moiety. With reasonable parameter choices, the model gives a good quantitative fit to the spectra observed for four carotenoids and at the same time accounts for the lack of structure in the long-wavelength absorption of retinal.